The effect of regular aerobic exercise on urinary brain-derived neurotrophic factor in children - Yunita Fediani; Masayu Rita Dewi; Muhammad Irfannuddin; Masagus Irsan Saleh; Safri Dhaini (Indonesian Pediatric Society Publishing House, 2014)
Background Nervous system development in early life influences the quality of cognitive ability during adulthood. Neuronal development and neurogenesis are highly influenced by neurotrophins. The most active neurotrophin is brain-derived neurotrophic factor (BDNF). Physical activity has a positive effect on cognitive function. However, few experimental studies have been done on children to assess the effect of aerobic regular exercise on BDNF levels. Objective To assess the effect of regular aerobic exercise on urinary BDNF levels in children. Methods This clinical study was performed in 67 children aged 6-8 years in Palembang. The intervention group (n=34) engaged in aerobic gymnastics three times per week for 8 weeks, while the control group (n=33) engaged in gymnastic only once per week. Measurements of urinary BDNF were performed on both groups before and after intervention. Mann-Whitney and Wilcoxon rank tests were used to analyze the differences between groups. Results There was no difference in urinary BDNF levels between the two groups prior to the intervention. After intervention, the mean urinary BDNF levels were significantly higher in the intervention group than in the control group, 230.2 (SD 264.4) pg/mL vs. 88.0 (SD 35.4) pg/mL, respectively (P=0.027). We also found that engaging in aerobic gymnastics significantly increased urinary BDNF levels from baseline in both groups (P=0.001). Conclusion Regular aerobic exercise can increase urinary BDNF levels and potentially improve cognitive function. Aerobic exercise should be a routine activity in school curriculums in combination with the learning process to improve children's cognitive ability.